High‐Normal Thyroid‐Stimulating Hormone Shows a Potential Causal Association With Arrhythmia Recurrence After Catheter Ablation of Atrial Fibrillation. Issue 14 (17th July 2018) - Morishima, Itsuro; Okumura, Kenji; Morita, Yasuhiro; Kanzaki, Yasunori; Takagi, Kensuke; Yoshida, Ruka; Nagai, Hiroaki; Ikai, Yoshihiro; Furui, Koichi; Yoshioka, Naoki; Tsuboi, Hideyuki; Murohara, Toyoaki
Abstract : Background: Hypothyroidism has been shown to contribute to enhanced atrial arrhythmogenesis, resulting in atrial fibrillation (AF) development in animal models and clinical populations. We aimed to elucidate whether high thyroid‐stimulating hormone (TSH) levels are related to outcomes of catheter ablation of AF. Methods and Results: Of 477 consecutive patients who underwent first‐time pulmonary vein isolation–based radiofrequency catheter ablation of AF, 456 with TSH above the lower limit of the normal range (age, 65.5±9.9 years; men, 73.9%; paroxysmal AF, 56.8%) were analyzed for this study. Atrial tachyarrhythmia recurrence for 3 years was compared across groups with hypothyroidism (n=23) and TSH quartile groups with euthyroidism (normal‐range TSH levels, n=433). Atrial tachyarrhythmia recurrence occurred in 179 patients (39%) after the first session. Patients with hypothyroidism had increased recurrence compared with patients with normal TSH levels (crude hazard ratio, 3.14 after the last session; P =0.001). When focusing on patients with normal TSH levels, recurrence‐free survivals after both the first and last sessions were significantly reduced in euthyroid patients with the highest quartile of TSH levels (quartile 4) compared with others (quartiles 1–3). Cox regression analysis identified high TSH levels as an independent predictor of atrial tachyarrhythmia recurrence after both the first (adjusted hazard ratio, 1.51; P =0.018) and last (adjusted hazard ratio, 1.86; P =0.023) sessions. The difference was more pronounced in patients with paroxysmal AF than in those with nonparoxysmal AF. Conclusions: Not only hypothyroidism but also high‐normal TSH levels may be an independent predictor of atrial tachyarrhythmia recurrence after catheter ablation of AF.